2018
DOI: 10.1167/18.8.7
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble perception of facial attractiveness

Abstract: Ensemble perception, the extraction of a statistical summary of multiple instances of a feature, enables efficient processing of information. Here we investigated whether ensemble representations can be formed for facial attractiveness, a socially important complex feature. After verifying that our face stimuli produced by geometric morphing represented a valid continuum of attractiveness (Experiment 1), we asked participants to compare the average attractiveness of four faces with a single probe face. Whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 55 publications
(108 reference statements)
1
23
1
Order By: Relevance
“…Similarly, Luo and Zhou 44 also identified limitations to the hierarchical encoding account of the cheerleader effect, while investigating ensemble coding in judgments of facial attractiveness. Notably, that observers showed a tendency to extract ensemble representations that were slightly less attractive than average attractiveness of each group 44 . Specifically referring to the cheerleader effect, Luo and Zhou 44 reasoned that if the ensemble representation was perceived to be highly attractive, observers should systematically overestimate, not underestimate, the average attractiveness of the group.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Similarly, Luo and Zhou 44 also identified limitations to the hierarchical encoding account of the cheerleader effect, while investigating ensemble coding in judgments of facial attractiveness. Notably, that observers showed a tendency to extract ensemble representations that were slightly less attractive than average attractiveness of each group 44 . Specifically referring to the cheerleader effect, Luo and Zhou 44 reasoned that if the ensemble representation was perceived to be highly attractive, observers should systematically overestimate, not underestimate, the average attractiveness of the group.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, even though the current study is the first to directly investigate the underlying cause of the cheerleader effect, the limitations of the hierarchical encoding mechanism have been alluded to previously 16,44 . Our findings provide the strongest evidence to date that hierarchical encoding appears to only make a minimal contribution to the cheerleader effect, if any at all.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evaluation of the central face was assimilated in the attractiveness of the surrounding faces, and the face in the middle was rated less attractive (Geiselman et al, 1984). This is in line with observers' bias toward the average attractiveness of the group by implicitly extracting information on it, when the target face is surrounded by a group of faces with heterogeneous degrees of attractiveness (Luo and Zhou, 2018). Rodway et al (2013) found both greater assimilation and greater contrast, with attractive faces perceived less attractive regardless of the attractiveness of the surrounding faces, and unattractive faces perceived more attractive only when flanked by other unattractive faces.…”
mentioning
confidence: 53%
“…It should be noted that we are not claiming ensemble coding cannot occur when there is no variance in the scene. For example, Luo and Zhou (2018) recently showed variability is not required for ensemble perception of facial attractiveness to arise.…”
Section: Discussionmentioning
confidence: 99%